Analisis Rute Distribusi Terpendek untuk Meminimumkan Biaya Distribusi Produk Kansteen dengan Metode Program Dinamis di CV XYZ - Shania Andra Fitriana; Dwi Sukma Donoriyanto (Ekonomis: Journal of Economics and Business, 2023)
CV XYZ is a company engaged in the concrete industry which produces products including paving blocks, hexagon paving, bishops, and kansteen. It is known that in October 2022 there was a high demand for kansteen products from Blora Regency, which consisted of six building shops as customers. The problem experienced by the company is that the delivery process is carried out by way of one delivery intended for one time order and transportation for only one type of product and for one customer this often causes repeated shipments with close time differences which causes distribution costs to increase. as well as the distribution routes that are traversed are also based on the driver's knowledge so that the distance traveled is not certain to be optimal which results in the use of fuel in excess of what it should be so that the costs incurred by the company increase which causes distribution costs to be not optimal. This study aims to determine the optimal distribution route so as to minimize distribution costs for kansteen products using the Dynamic Programming method. The stages that were passed in this study began with the process of formulating the problem, collecting data, processing data using the Dynamic Programming method assisted by the WinQSB software to determine the shortest route, then determined the calculation of the optimal distribution cost as a recommendation for improvement. Based on the research results, it was found that the proposed route distance used the Dynamic Programming method and optimal distribution costs, namely for TB A was 82.81 Km with optimal distribution costs of IDR 1,683,906, -; TB B is 53.65 Km with an optimal distribution cost of IDR 1,980,824, -; TB C is 60.19 Km with an optimal distribution cost of IDR 1,020,060; TB D is 60.89 Km with an optimal distribution cost of IDR 1,279,045; TB E is 48.5 Km with an optimal distribution cost of IDR 967,068, -; and TB F is 60.69 Km with an optimal distribution cost of IDR 766,746. Recommendations for proposed improvements that can be made by the company are by rearranging product distribution routes to make it more optimal and implementing a minimum order system in order to reduce the intensity of multiple shipments as a result of purchasing products with too little quantity on each order so that distribution costs become optimal.